Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Kooperatif Tipe Team Assisted Individualization - Riskimar Taha; Syamsu Qamar Badu; Arfan Arsyad (Jambura Journal of Mathematics Education, 2022)
This study aims to improve student learning outcomes by using the Team Assisted Individualization (TAI) cooperative learning model in statistical material in class X ATPH-1 SMK Gotong Royong. This type of research is Classroom Action Research (CAR). The research design used is the design of Kemmis and Mc. Taggart. The data collected in each research activity were analyzed descriptively using the percentage technique. The data includes student activity data, student learning outcomes, and teaching activities in implementing the TAI-type cooperative learning model. The results showed that there was an increase in student activity in learning with a percentage of 87.5%, teacher activity also increased by a percentage of 89.46% and student learning outcomes also experienced an increase which scored above 75 as many as 15 people with an average percentage of 85 % while those who scored below 75 or incomplete were 2 people with an average percentage of 15%. So in the first cycle of student activity and the average student learning outcomes have met the indicators of the success of the action.